2023
DOI: 10.1063/9.0000430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of casting methods on magnetic properties of Sm(CoFeCuZr)z magnet

Abstract: The effect of casting method on the magnetic properties of Sm(Co0.63Fe0.28Cu0.07Zr0.02)7.6 magnet has been investigated. The results show that the plate-mold ingot (PM) and strip-casting flake (SC) have the same phase composition. Compared with PM, the SC has a smaller grain size and larger fine-grain region due to its larger degree of undercooling. The magnetic properties of the PM magnet are Br = 11.63 kG, Hcj = 25.65 kOe, (BH)max = 30.97 MGOe, while the magnetic properties of SC magnet are Br = 11.45 kG, Hc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…As the strip casting parameters were not given and limited microstructural analysis was presented, no direct comparisons can be made regarding the optimisation of the strip casting process. Yang et al and Yang et al [20,21] demonstrated very similar findings to Meng et al [19], showing that slower wheel speeds in strip casting led to better magnetic properties; however, as Meng et al, were utilising the full manufacturing route for magnet processing and were not aiming to circumvent the long heat treatment as would be the aim of this work. Likewise, direct comparison with Zheng et al [22] is limited as they did not optimise the strip casting process; however, they obtained a similar combination of phases of the alloy but were not able to demonstrate directional columnar growth from the wheel side to the free side of the flake as presented in this work.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…As the strip casting parameters were not given and limited microstructural analysis was presented, no direct comparisons can be made regarding the optimisation of the strip casting process. Yang et al and Yang et al [20,21] demonstrated very similar findings to Meng et al [19], showing that slower wheel speeds in strip casting led to better magnetic properties; however, as Meng et al, were utilising the full manufacturing route for magnet processing and were not aiming to circumvent the long heat treatment as would be the aim of this work. Likewise, direct comparison with Zheng et al [22] is limited as they did not optimise the strip casting process; however, they obtained a similar combination of phases of the alloy but were not able to demonstrate directional columnar growth from the wheel side to the free side of the flake as presented in this work.…”
Section: Discussionsupporting
confidence: 62%
“…For all strip cast alloys, however, the phase distribution changed substantially to consist predominantly of the metastable 1:7H phase with small amounts of 1:5H phase and trace 2:17R phase. Due to the substantially increased cooling rate, the microstructure typically consisted of a nucleation zone where the melt started to solidify in contact with the wheel and columnar growth along the thermal gradient from the wheel side of the flake towards the free side, similar to that demonstrated by Meng et al [19] and Yang et al [20]. However, in a number of flakes, there were regions where the cooling rate was not sufficient to maintain columnar growth, resulting in non-directional growth towards the free side of the flake and elemental segregation similar to that observed in the as-received cast alloy.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations